2022
DOI: 10.3961/jpmph.22.123
|View full text |Cite
|
Sign up to set email alerts
|

Inequality in Private Health Care Expenditures: A 36-Year Trend Study of Iranian Households

Abstract: Objectives: Throughout history, societies have been impacted by inequality. Many studies have been conducted on the topic more broadly, but only a few have investigated inequalities in out-of-pocket health payments (OHP). This study measures OHP inequality trends among the Iranian households.Methods: This study used data from the Iranian Statistics Center on Iranian household income and expenditures. The analysis included a total of 995 300 households during the 36 years from 1984 to 2019. The Gini coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“… 14 Inequality in health service utilization not only affects individuals, but also has a negative impact on labor market productivity and ultimately, gross domestic product. 15 There is clear evidence showing that healthcare services utilization has not been equally distributed among different socioeconomic groups 16 - 18 that goes against basic human rights. 4 , 19 , 20 Studies conducted in both developed and developing countries have demonstrated that residents in affluent areas are more likely to utilize health services when they become sick compared to their counterparts in poorer areas.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Inequality in health service utilization not only affects individuals, but also has a negative impact on labor market productivity and ultimately, gross domestic product. 15 There is clear evidence showing that healthcare services utilization has not been equally distributed among different socioeconomic groups 16 - 18 that goes against basic human rights. 4 , 19 , 20 Studies conducted in both developed and developing countries have demonstrated that residents in affluent areas are more likely to utilize health services when they become sick compared to their counterparts in poorer areas.…”
Section: Introductionmentioning
confidence: 99%
“…This may have an impact on the efficiency of the health care system. Therefore, the status of OPHP will not only determine households' access to health care services, but can also affect their well-being through income allocation to health care and other needs (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in 2011 an exchange rate shock in Iran, severely damaged people's purchasing power and reduced their capacity to pay for health care (5), including for those who had indispensable and continuous need for health care services, such as people with disabilities or rare diseases. As a result, health services may be pushed out of affordability for some families.…”
mentioning
confidence: 99%